CESAREAN AUDIT: USING ROBSON’S 10 GROUP CLASSIFICATION AT C. U. SHAH MEDICAL COLLEGE AND HOSPITAL - HIMANI MAL; HARSHDEEP K JADEJA; BHAVESH B AIRAO (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The World Health Organization (WHO) has expressed concern over the rising cesarean section (CS) rate, particularly in middle-and high- income countries. The reasons behind this increase are still debated, but the WHO declared that there is no justification for a rate higher than 10–15%. The Robson classification system, advocated by WHO and FIGO, can help assess and compare CS rates. Study Design and Methods: The Gynecology Department at C.U. Shah Medical College and Hospital conducted an observational study on pregnant patients hospitalized for labor pain between January 2020 and December 2022, with a focus on CS patients. The study used Robson’s 10-group categorization technique to extract maternal features and categorize cesarean performances. Results: Between January 2020 and December 2022, C. U. Shah Medical College and Hospital delivered 4967 patients, of whom 1,572 underwent a CS section. 46.3% were nulliparous, and 53.7% were multipara. 78.31% of patients arrived at full term, with 98.8% having single conceptions. 94.8% of the cases had a cephalic presentation, 4.4% had a breech presentation, and 0.81% had a transverse position. Conclusions: Robson classification is a useful technique for analyzing cesarean delivery (CS) rates, aiding in identifying corrective methods to reduce burden on healthcare systems, and promoting accurate labor monitoring, fetal scalp electrodes, and prenatal education.